1984
DOI: 10.1192/bjp.144.5.482
|View full text |Cite
|
Sign up to set email alerts
|

Interactional Correlates of Expressed Emotion in the Families of Schizophrenics

Abstract: Measures of intrafamilial expressed emotion (EE) predict relapse in schizophrenic patients, but previous research has not investigated whether EE scores are representative of ongoing family transactions. Parents of 42 hospitalized schizophrenic patients were rated for level and type of EE. Following the patient's discharge, families participated in two 10-minute direct interaction tasks. Transcripts from these interactions were coded on dimensions of affective communication. High-EE parents exhibited more nega… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
133
3
7

Year Published

1988
1988
2012
2012

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 195 publications
(153 citation statements)
references
References 14 publications
10
133
3
7
Order By: Relevance
“…The adolescents and caregivers were asked to discuss the adolescents' ideas and opinions concerning educational or professional plans for 10 min. This procedure is similar to other interaction assessments used in family studies of patients with schizophrenia and has been found to differentiate between families with high EE and low EE [26,27,28]. The interactions were videotaped for later head position coding.…”
Section: Methodsmentioning
confidence: 99%
“…The adolescents and caregivers were asked to discuss the adolescents' ideas and opinions concerning educational or professional plans for 10 min. This procedure is similar to other interaction assessments used in family studies of patients with schizophrenia and has been found to differentiate between families with high EE and low EE [26,27,28]. The interactions were videotaped for later head position coding.…”
Section: Methodsmentioning
confidence: 99%
“…Parental CRIT has also correlated positively with "belittling and blaming" statements made by parents, and negatively with "disclosing and expressing" and "trusting and relying" (Hubschmid & Zemp, 1989). The way that EOI relates to interactions between parents/ relatives and patients has generally been less consistent across the literature compared to CRIT (Miklowitz et al, 1984;Mueser et al, 1993). Some studies have found that high EOI parents make more intrusive statements (Strachan et al, 1986) or more ambiguous and unclear statements (Hubschmid & Zemp, 1989); others have found that they do not differ in behavioral interactions compared to low EOI parents .…”
mentioning
confidence: 96%
“…The measure also has not demonstrated cohesiveness as a measure, in terms of its internal consistency and the way that the individual criteria relate to child psychopathology (McCarty & Weisz, 2002). To increase our understanding of the appropriateness of applying EOI to child clinical samples, investigation of its concurrent validity with behavioral data is warranted.Thus far, the research relating observed interactions to EE has mostly focused on families of adults with or at risk, for schizophrenia-spectrum disorders (Miklowitz, Goldstein, Falloon, & Doane, 1984;Strachan, Goldstein, & Miklowitz, 1986;Valone, Norton, Goldstein, & Doane, 1983;) bipolar disorder (Simoneau, Miklowitz, & Saleem, 1998), or depression (Mundt, Fiedler, Ernst, & Backenstrab, 1996 and has assessed interactions between relatives as a function of overall EE in general, not differentiating CRIT from EOI The studies that have assessed the two EE components separately suggest that relatives high on the CRIT dimension express a significantly greater number of criticisms during interactions than relatives who score low on this dimension, and show extreme negative escalation patterns . Parental CRIT has also correlated positively with "belittling and blaming" statements made by parents, and negatively with "disclosing and expressing" and "trusting and relying" (Hubschmid & Zemp, 1989).…”
mentioning
confidence: 99%
“…Birchwood (1983) found that the coping strategies employed to deal with behavioural disturbance commonly found in schizophrenia appeared to be associated with the subsequent course of the condition. Miklowitz et al (1984) showed that the critical and over-involved attitudes expressed in the Camberwell Family Interview were, indeed, markers of critical and intrusive behaviours in actual family problem solving discussions. It has been noted that the EE levels, especially criticism, peak during the patient's florid episode and decline once the florid symptoms and associated behaviour disturbance remit.…”
Section: Factors Provoking High Ee Responsesmentioning
confidence: 99%